Noncontingent Reinforcement to Improve Classroom Behavior of a Student With Developmental Disability. (July 2016) - Moore, Tara C.; Robinson, Christina C.; Coleman, Mari Beth; Cihak, David F.; Park, Yujeong
The purpose of this study was to examine the effects of a noncontingent reinforcement intervention package implemented by an interning teacher in a special education classroom to address disruptive behavior and task engagement for a third-grade, 8-year-old boy with developmental disability. Using a within-subject reversal design (A-B-A-B), a teacher interning in Max's classroom delivered 3-min breaks (i.e., escape) from classroom tasks on a fixed-time 2-min interval schedule for five daily sessions during the first intervention phase and for five daily sessions during the reimplementation phase; breaks were not contingent on his behavior. The intervention package also included a reinforcement menu for the student to select daily from escape activities (i.e., preferred activities including swinging and taking a walk) and a picture prompt to provide a continuous, visual reminder of the upcoming reinforcer. Results indicated increases in task engagement and decreases in disruptive behavior during phases when the intervention was applied. Implications for future research and practice are discussed.